The Relationship Between Length of Rehabilitation and Quality of Life for Psychoactive Substance Users in Yogyakarta - Ani Kristiyani (Duta Pharma Journal, 2022)
The background of this research is the use of psychoactive substances causes complex problems and becomes a threat to the state. Rehabilitation can reduce the risk of relapse of psychoactive substance abuse and the risk of crime, thereby improving quality of life. Understanding rehabilitation with quality of life has a positive impact on users of psychoactive substances. Therefore, it is essential to study the relationship between the length of rehabilitation and the quality of life of users of psychoactive substances. The purpose of this study was to determine the relationship between the size of rehabilitation and the quality of life for users of psychoactive substances. This research method is a non-experimental observational analytic study with a cross-sectional design. The subjects of the study were users of psychoactive substances who were undergoing the rehabilitation process at the Class IIA Narcotics Prison in Yogyakarta. Quality of life was measured by the World Health Organization Quality of Life BREF (WHOQOL-BREF) instrument. The significance level of the statistical test was stated at p<0.05. Data analysis used the Spearman Rank correlation test and multiple linear regression. The results of this study carried out for two months (March to April 2021) obtained a total of 77 subjects using psychoactive substances. The length of rehabilitation has a significant positive correlation with the quality of life, indicated by the value of p = 0.048 (p <0.05) and r = 0.220, which means that the longer the respondent undergoes rehabilitation, the better the quality of his life. This study concludes that there is a significant relationship between the length of repair and quality of life for users of psychoactive substances.